ANALISIS DAERAH RAWAN KECELAKAAN LALU LINTAS (BLOCK SPOT) DIJALAN YOGYAKARTA – PARANGTRITIS KABUPATEN BANTUL - Itsnaini Aziz; Widarto Sutrisno; Dimas Langga Candra Galuh; Tri Ardianto (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2025)
As the number of vehicles increases with the increase in world population, the vehicle density on this road continues to increase every year. year. . Therefore, the large number of traffic accidents that frequently occur on highways poses challenges for all traffic participants. The research method used is survey and collection. data. . From the results of data analysis and discussion, after performing many calculations and analyzing traffic accident data on the Yogyakarta - Prangtritis route, Bantul district, the location and number of black spots were found. Accidents occurred on Yogyakarta - Prangtritis road, Bantul Regency, including research results on the level of compensation between accident incidents and factors affecting them, proposed solutions to reduce the number accident on the highway and have the ability to make repairs so that no more accidents occur.